The Usability of Passenger Delay Models in Socio-Economic Analysis - Thorhauge, Mikkel (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
The following paper discusses how a passenger delay model can be used in socio-economic calculations. At present passenger delays are often omitted in the modeling phase and therefore not included in the socio economic analysis. By using a passenger delay model passenger delays can be included in a cost-benefit analysis. Including passenger delays in the cost-benefit analysis will increase the level of details and thereby improve the accuracy of socio-economic analysis. In this paper the third generation passenger delay model is used. This model is the newest and most detailed passenger delay model created so far. When using a passenger delay model, the main problem is how to properly include the delays in a socio- economic analysis. This is due to the fact that passenger delays are not necessarily unambiguously. In general, delays can occur on different parts of a journey; while the passengers are waiting for the train (waiting time, first waiting time or even hidden waiting time) or while the passenger are sitting in the train (or bus). Furthermore a delay can also be negative, meaning that a passenger will arrive before planned (a so-called negative delay). This article proposes that a delay is defined solely by the difference between the scheduled and realized arrival time. The recommendations are listed as follows: The value of time for a delay is defined as done by the Danish Ministry of Transport (Trafikministeriet, 2003) no matter how or when the delay has occurred. The size of the delay is calculated solely by the difference between the planned and realized arrival time. A negative delay is defined as the value of time of hidden waiting time. A negative delay is calculated as the difference between the planned and realized arrival time and is considered a surplus in the cost benefit analysis. A delay will not be included if the passenger arrives at his or her final destination on time even though the passenger may have experienced a delay (or travelled along a different route than planned) during the journey. Note that this paper is regarded as a prequel to the article “Optimization of timetable supplement from a passenger based socio-economic point of view” (Thorhauge, 2010). This article is based on the results of (Thorhauge & Piester, 2010).